Purification and Characterisation of the 33-Kilodalton Outer Membrane Protein of Pasteurella Multocida Type 6:B - Zainal Abidin, Zamirah (2002)
The 33-kiloDalton (kDa) outer membrane protein (OMP) of Pasteurella multocida 6:B strain C82 was purified from the crude OMP extract, and its characteristics were investigated. The crude OMP extract was prepared from P. multocida 6:B grown in iron-restricted condition, using Sarkosyl extraction method. The purification was carried out by means of modified cylindrical preparative SDS-PAGE, and the purity of the 33kDa OMP was evaluated by SDS-PAGE gels. The protein was present as a single band when re-run on SDS-PAGE gels stained with Coomassie brilliant blue R-250 and silver staining. However, judged from the 2-keto-3-deoxyoctonic acid (KDO) assay and also Western blotting results, it was observed that the purified 33kDa OMP was not completely devoid of lipopolysaccharide (LPS) and other contaminating proteins, which leads to conclusion that this particular protein was not purified to homogeneity. Comparisons in terms of efficiency of purification and yield from the crude extract between modified cylindrical preparative SDSPAGE and diethylaminoethyl-ion exchange chromatography (DEAE-IEX) was investigated. It was found out that the former was more superior, being less tedious to be carried out and had lower LPS contamination. Protection studies showed that the 33kDa OMP afforded 20% protection level in mice. The ELISA antibody titres did not correspond to protective immunity, which means that the antibody produced was not protective against live challenge with P. multocida 6:B. This leads to conclusion that 33kDa OMP is not protective. This finding could be attributed to the harsh denaturation process during purification of the 33kDa OMP, rendering it being devoid of its protective capacity. N-terminus amino acid sequencing and composition analysis of the 33kDa OMP revealed that it was similar to P. multocida major OMP, protein H , which was previously characterised as a porin. However, it was doubtful to conclude 33kDa OMP as porin, since it was not protective, and this warrants for more detailed analyses to verify the function(s) of this protein.